2015
DOI: 10.1007/s00442-015-3337-z
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the phylogenetic structure of arbuscular mycorrhizal fungi in response to experimental nitrogen and carbon dioxide additions

Abstract: Global N inputs and atmospheric CO2 concentrations have increased as a result of human activities, and are predicted to increase along with population growth, with potentially negative effects on biodiversity. Using taxonomic and phylogenetic measures, we examined the response of arbuscular mycorrhizal fungi (AMF) to experimental manipulations of N and CO2 at the Jasper Ridge Global Change Experiment. No significant interactions between N and CO2 were observed, but individual effects of N and CO2 were found. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…In our study, N fertilizer did not significantly changed AMF diversity in the wheat rhizosphere, consistent with previous reports (Mueller and Bohannan, 2015;Dueñas et al, 2020). This may reflect the influence of interaction between fertilization and plant on rhizosphere AMF, as the relocation of C to AMF increased with N fertilization.…”
Section: Long-term Nutrient Addition Effects On Rhizosphere Amf Specisupporting
confidence: 92%
“…In our study, N fertilizer did not significantly changed AMF diversity in the wheat rhizosphere, consistent with previous reports (Mueller and Bohannan, 2015;Dueñas et al, 2020). This may reflect the influence of interaction between fertilization and plant on rhizosphere AMF, as the relocation of C to AMF increased with N fertilization.…”
Section: Long-term Nutrient Addition Effects On Rhizosphere Amf Specisupporting
confidence: 92%
“…However, there is no consensus on how AM fungal communities respond to N deposition. Many studies found that N addition decreased the abundance, richness and diversity of AM fungi (Antoninka et al, 2011;Egerton-Warburton & Allen, 2000;Williams et al, 2017), whereas many others also found positive effects (Jefwa et al, 2006;Porras-Alfaro et al, 2007;Zheng et al, 2014) or no effects (Eom et al, 1999;Mueller & Bohannan, 2015;van Diepen et al, 2011). These discrepancies in the effects of N addition on AM fungal communities might be due to the differences in soil resource availability (N and P), host plants (composition and diversity) and experimental variables (the form, amount and duration of N addition).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are ubiquitous in terrestrial ecosystems. They are obligate plant root symbionts found in more than 80% of plant families (Mueller and Bohannan 2015 ) and they provide multiple benefits for both plant and AMF. For instance, AMF can provide plants with critical nutrients (Hodge et al 2010 ) and non-nutrient benefits (Walder and van der Heijden 2015 ), help plants withstand drought (Li et al 2013 ), develop soil aggregates (Rillig and Mummey 2006 ), stimulate photosynthesis (Kaschuk et al 2009 ) and increase plant productivity (Maček et al 2011 ), thereby influencing ecosystem processes and agricultural sustainability (Rillig 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The plant, in turn, provides photosynthetic carbon (C) as an energy source for AMF, which can alter the fungal community (Kim et al 2015 ). In addition to beneficial effects on plants, AMF also enhance ecosystem sustainability by influencing numerous soil properties and structure (Wilson et al 2009 ), including soil stability (Mueller and Bohannan 2015 ), C storage (Treseder and Allen 2000 ), soil moisture (Johnson et al 2003 ), and nitrogen (N), C and phosphorus (P) cycles (Van Der Heijden et al 2008 ). Lower AMF biodiversity can also lead to unsustainable crop production and ecosystem instability (Maček et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%